Colorectal anastomotic leakage corrected by transanal laparoscopy. (8th June 2016) - Dapri, G.; Guta, D.; Grozdev, K.; Antolino, L.; Bachir, N.; Jottard, K.; Cadière, G.‐B.
Abstract: Aim: Interest in transanal laparoscopy has increased in the last decade. This approach can allow primary procedures such as polypectomy, total mesorectal excision and the treatment of postoperative complications such as bleeding, leakage and fistula formation. Method: Two patients treated by transanal repair for leakage of a colorectal anastomosis after laparoscopic anterior resection of the rectum are reported. The first developed leakage immediately during the surgery and in the second leakage presented at 4 weeks. A new transanal platform according to DAPRI (Karl Storz‐Endoskope, Tuttlingen, Germany), formed by a reusable port and reusable monocurved instruments was developed to permit manipulation of sutures introduced via the anus in a maximally ergonomic manner. Laparoscopic suturing was performed transanally and a protective ileostomy was added as well. Results: The transanal procedures took 60 and 45 min and the patients were discharged after 5 days and 2 days. At 2 months both defects were found to be healed on contrast radiology and endoscopy; therefore the ileostomy was closed. Anal function was satisfactory with a frequency of two and one times per 24 h with no incontinence or evidence of sepsis. Conclusion: Intra‐operative or late leakage of colorectal anastomosis can be safely treated by transanal laparoscopy. This new transanal platform offers the surgeon the possibility to work in ergonomic positions, without increasing the cost of the procedure thanks to the reusable nature of the material used.